2018
DOI: 10.1016/j.jogn.2017.04.131
|View full text |Cite
|
Sign up to set email alerts
|

Universal Postpartum Mental Health Screening for Parents of Newborns With Prenatally Diagnosed Birth Defects

Abstract: Incorporating the screening process into routine nursing practice with immediate mental health triage and referral made the program feasible. The risk factors identified add to the growing knowledge about parents of newborns in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…In the postpartum period, there is an increased risk of suffering, especially among mothers of newborns with confirmed malformations, who will stay hospitalized after birth. Therefore, the early identification of psychological distress in this period and the referral to mental health care providers within the obstetric environment are essential 12 . …”
Section: Introductionmentioning
confidence: 99%
“…In the postpartum period, there is an increased risk of suffering, especially among mothers of newborns with confirmed malformations, who will stay hospitalized after birth. Therefore, the early identification of psychological distress in this period and the referral to mental health care providers within the obstetric environment are essential 12 . …”
Section: Introductionmentioning
confidence: 99%
“…Several evidence-based strategies assist mothers in coping with mental health complications during NICU hospitalization and increase parent visitation and engagement. These strategies include free community classes during pregnancy and NICU hospitalization to address the stressors of parenting in the NICU (Puthussery, Chutiyami, Tseng, Kilby, & Kapadia, 2018), scheduling peer advisors to have frequent meetings with NICU parents to address concerns (Bourque et al, 2018;Hall et al, 2015;Levick, Quinn, & Vennema, 2014;Rossman et al, 2015), and universal screening for mental health complications (e.g., acute stress disorder, post-traumatic stress disorder, depression, and anxiety) upon NICU admission, 14 days of life, and sequentially thereafter with trained mental health professionals (Cherry et al, 2016;Cole, Olkkola, Zarrin, Berger, & Moldenhauer, 2018;McCabe-Beane, Stasik-O'Brien, & Segre, 2018).…”
Section: Clinical Strategies To Buffer Stressmentioning
confidence: 99%
“…Acceptability data was not reported by measure but the importance of length was noted, due to time and also the cognitive and affective load for participants. Similarly, another study (95) found that fathers of newborns in specialist-NICU were receptive to screening during the mother's hospitalization (using the IES-R and CES-D), with 79.6% "compliance" (and 96.5% in mothers). In a pediatric intensive care unit setting, screening parents for vulnerability to PTSD [using the Post-traumatic Adjustment Screen (99)] was reported as acceptable to parents, with; 85% of those that went on to complete the questions not reporting any distress in completing the measure; however, only 52% of families consented to complete the questions (81).…”
Section: Summary Of Findings: Evidence Of Acceptability Of Specific Mmentioning
confidence: 86%
“…Parent perspectives were reported in eight studies (34,49,(78)(79)(80)(81)(82)(83); nine reported health professional perspectives (84-92); none included both. A further three feasibility and implementation studies reported behavioral indicators (e.g., completion rates) without collecting participants' perspectives (93)(94)(95).…”
Section: Overview Of Included Acceptability Studiesmentioning
confidence: 99%
See 1 more Smart Citation